2020
DOI: 10.7150/thno.47746
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng saponins modulate the gut microbiota to promote thermogenesis and beige adipocyte reconstruction via leptin-mediated AMPKα/STAT3 signaling in diet-induced obesity

Abstract: Background: Activation of the thermogenic program in white and brown adipocytes presents a promising avenue for increasing energy expenditure during the treatment of obesity. The endogenous mechanism for promoting thermogenesis in brown adipocytes or browning in white adipocytes has indicated that the gut microbiota is a crucial regulator of the host energy balance. However, whether the effects of the therapeutic intervention-induced modulation of the gut microbiota on adipocyte browning involved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 82 publications
4
93
1
Order By: Relevance
“…Parabacteroides is a commensal bacterium in the gut that is negatively related to obesity [ 42 , 43 , 44 , 45 ] and plays a role in anti-inflammatory processes [ 46 , 47 ]. Treatment with Parabacteroides distasonis has been reported to ameliorate metabolic dysfunction and alleviate obesity in HFD-fed mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parabacteroides is a commensal bacterium in the gut that is negatively related to obesity [ 42 , 43 , 44 , 45 ] and plays a role in anti-inflammatory processes [ 46 , 47 ]. Treatment with Parabacteroides distasonis has been reported to ameliorate metabolic dysfunction and alleviate obesity in HFD-fed mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, increasing evidence indicates that adult humans also possess Ucp1-positive BAT 4 , 5 , which contributes to metabolic homeostasis. Such findings have uncovered a viable therapeutic strategy, where these cells are exploited to treat obesity and diabetes 6 , 7 . Thus, understanding the regulatory mechanism that drives BAT thermogenic activity now has clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, acute intraperitoneal injection of Rb1 activates the PI3K/Akt signaling pathway through the expression of c-FOS in brain regions involved in energy homeostasis, and inhibits the expression of NPY gene in the hypothalamus, thereby reducing appetite and food intake, body weight, and body fat content and increasing energy consumption ( Xiong et al, 2010 ; Park H. J. et al, 2019 ). Xu et al also found that PNS-induced regulation of intestinal flora in DIO mice can increase BAT thermogenesis and beige adipocyte reconstruction by activating the leptin-AMPK/STAT3 signaling pathway thus promoting energy consumption ( Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%